Relationship Between Sleep Apnea and Coronary Artery Calcium in Patients With Ischemic Stroke - Cho, Kyoo Ho; Lee, Dong Hyun; Kim, Kyung Min; Choi, Yun Ho; Nam, Hyo Suk; Heo, Ji Hoe; Heo, Kyoung; Kim, Young Dae (Frontiers in Neurology, 2019)
Study Objectives: Coronary artery disease is considered to be the major cause of death amongst patients with ischemic stroke. The coronary artery calcium (CAC) score is related not only to sleep-disordered breathing, but also with future risk of cardiovascular mortality. We investigated the association between the severity of sleep-disordered breathing and CAC score in patients with ischemic stroke. Methods: We included 32 patients who underwent coronary multichannel computed tomography and polysomnography (within 2 years of the stroke event) amongst the patients admitted to our clinic due to acute ischemic stroke. We investigated vascular risk factors, polysomnography findings, and sleep questionnaire scores, and their relationships with the CAC score. Results: All patients were found to have sleep apnea of any degree, and 32 (72%) had severe sleep apnea. Twenty-three (72%) patients had a positive CAC score. Higher CAC scores were associated with elevated respiratory disturbance index (RDI), apnea index, oxygen desaturation index, and STOP-BANG test scores. Multivariate analysis after adjusting for potential confounding factors revealed independent relationships between the CAC score and the RDI (ß [SE] = 5.3 [2.1], p=0.01), oxygen desaturation index (ß [SE] = 6.8 [2.8], p=0.02), and STOP-BANG test score (ß [SE] = 90.3 [37.7], p=0.02). Conclusion: Our findings indicate a relationship between coronary atherosclerotic burden measured by the CAC score and the severity of sleep apnea. Performing polysomnography could be useful for investigating the severity of hidden coronary artery disease among these patients.